Use of drones to monitor water availability and quality in irrigation canals and reservoirs for improving water productivity and enhancing precision agriculture in smallholder farms - Mabhaudhi, Tafadzwanashe; Bangira, T.; Sibanda, M.; Cofie, Olufunke O. (CGIAR Initiative on West and Central African Food Systems Transformation, 2022)
The report provides a methodology protocol for measuring temporal and spatial changes in water quantity and quality using drone imagery. The procedure is informed by the need for effective and sustainable water resource use to enhance water productivity under climate change. It is based on a literature review that allows the identification of appropriate processes, materials, and procedures for water monitoring, including mapping spatial and temporal dynamics of reservoirs, measurement of water quality parameters, and flood mapping of irrigation canals.